Work Engagement and Psychological Capital as Determinants of Employee Performance: The Mediating Role of Organizational Commitment in Indonesian Retail Employees - Fahmi Sulaiman; Jihan Sulaiman (Fundamental and Applied Management Journal, 2026)
This study investigates how work engagement and psychological capital relate to employee performance and whether organizational commitment explains part of these relationships in Indonesia's retail sector. The research used an explanatory quantitative approach with questionnaire data from 90 employees working in a retail company in North Sumatra, Indonesia. The data were processed with Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. The analysis shows that work engagement (β = 0.28, p = 0.004) and psychological capital (β = 0.26, p = 0.008) significantly improve employee performance. Both predictors also contribute to organizational commitment (β = 0.34 and β = 0.31), and commitment has a substantial positive relationship with performance (β = 0.40, p < 0.001). The indirect effects indicate that organizational commitment acts as a partial mediator between work engagement and employee performance (indirect effect = 0.14, p = 0.014) and between psychological capital and employee performance (indirect effect = 0.12, p = 0.021). The model accounts for 55% of organizational commitment and 62% of employee performance. Because the study uses one organization and self-assessed responses, the findings should be generalized carefully. Future studies are advised to use wider samples and multiple sources of performance data. The article contributes by combining engagement, psychological capital, commitment, and performance in one empirical framework for Indonesian retail employees.